Perlindungan Hukum terhadap Promotor atas adanya Wanprestasi yang dilakukan oleh Investor dalam penyelenggaraan Acara Festival Pesta Rakyat 2023 - Meutuah, Ratu; Qomarudin, Heri (HUMANIORUM, 2025)
An increasing number of Indonesians are now interested in creatively packaged music events. One such event, the 2023 People's Festival, was organized by PT MSR as a promoter, and designed as an educational entertainment experience. Recognizing its significant development potential, PT AM expressed interest in collaborating with PT MSR on its organization. The two parties agreed upon an investment contract. However, during the short planning period, PT AM, as the investor, committed a breach of contract. While preparations continued, PT MSR incurred losses due to responsibilities towards contracted vendors. PT MSR is entitled to seek accountability from PT AM as stipulated in the agreement. Despite this, PT AM has not acted in good faith to resolve the issues, creating disputes over the mutually agreed-upon contract.